Dampak Sosial dan Politik Kasus Korupsi E-KTP Setya Novanto terhadap Kepercayaan Publik pada E-Government di Indonesia - Khalifa Nur Khaliq Pohan; Rahma Apasha; Kanina Aufia Hanindita; Fatkhuri (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2025)
This research aims to examine the social and political impact of the corruption case of the Electronic Identity Card (E-KTP) project on the level of public trust in the implementation of e-government in Indonesia. The approach used is descriptive qualitative, with data collection through desk study and document analysis from sources such as mass media, official reports, and academic literature. The research findings show that the case has dealt a serious blow to public perceptions of the government's capacity to manage digital projects in a transparent and accountable manner. The social impact of this case is reflected in the increasing public apathy towards digital reform programs, as well as the strengthening of negative stigma against public officials. From a political perspective, the scandal has weakened the legitimacy of state institutions that play a role in data management and technology-based public services. The research asserts that transparency, integrity and accountability are key pillars in building public trust in digital government systems. Restoring trust requires comprehensive reforms in digital governance and strengthening the capacity and integrity of institutions involved in the delivery of information technology-based public services